Willingness to Pay Analysis of First Fuel in Yogyakarta - Masniya Khairunnisa; Lilies Setiartiti (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to measure the value of willingness to pay and analyze the factors that affect consumer willingness to pay toward Pertamax fuel. This study's dependent variable is income, number of owned vehicles, the frequency of vehicle use, and product literacy. In this study sample of 100 Pertamax fuel users in Yogyakarta were selected using the Purposive Sampling method. This study using multiple linear regression or Ordinary Least Square (OLS). The results show that the value of consumer willingness to pay toward Pertamax fuel is Rp. 10,545. The factors that influence willingness to pay are income, frequency of vehicle use, and product literacy. These three variables are positive and have a significant influence on consumer willingness to pay toward Pertamaxfuel. While the variable number of the owned vehicle